2020
DOI: 10.3389/fpsyt.2020.00138
|View full text |Cite
|
Sign up to set email alerts
|

Family Features of Social Withdrawal Syndrome (Hikikomori)

Abstract: Background: Family may play an important role in the origin, maintenance, and treatment of people with social withdrawal. The aim of this study is to analyze family factors related to social withdrawal syndrome. Methods: Socio-demographic, clinical, and family data, including family psychiatric history, dysfunctional family dynamics, and history of family abuse were analyzed in 190 cases of social withdrawal with a minimum duration of 6 months that started an at-home treatment program. Data were analyzed at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…A French study showed nearly half of people with hikikomori had no professional assistance until they received home visit support (Chauliac et al, 2017). The first interview was conducted with the family or caregiver in over 70% of cases in a Spanish study (Malagón-Amor et al, 2020). However, the person with hikikomori who accepted and attended the initial visit had better outcomes, including decreasing problematic behaviours, and ensuring regular attendance/completed treatment, than those who refused the first visit (Imai et al, 2020; Kondo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A French study showed nearly half of people with hikikomori had no professional assistance until they received home visit support (Chauliac et al, 2017). The first interview was conducted with the family or caregiver in over 70% of cases in a Spanish study (Malagón-Amor et al, 2020). However, the person with hikikomori who accepted and attended the initial visit had better outcomes, including decreasing problematic behaviours, and ensuring regular attendance/completed treatment, than those who refused the first visit (Imai et al, 2020; Kondo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2013) reported that due to difficulties in meeting clients, well-trained caseworkers visited each client’s home to interview both the client and their parents using a structured manual. There are reports in which the home visitation support team consisted of mental health personnel (Lee et al, 2013; Malagón-Amor et al, 2020). Further evidence is needed regarding the training of home visiting workers for people with hikikomori.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies indicate, for instance, that auto-isolation, a common reaction of adolescents to certain stressful situations, including bullying, enhances psychopathological risk [ 109 ]. A pathological condition whose incidence has strongly increased in the internet era due to the rise of cyberbullying situations [ 110 ], is clinically linked to auto-isolation and has been recently proposed to be admitted into the DSM-5 [ 111 , 112 ]. Isolation-related stress supports the importance of social connections as functional to survival in mammals — the absence of a solid social network is a predisposing factor impacting emotional well-being [ 113 ].…”
Section: Psychological Stressmentioning
confidence: 99%
“…6 However, increasing reports from around the world provided a better understanding of this condition and suggested that hikikomori is a global health problem, which may exist as an independent primary diagnosis. 7,8 The elemental attribute of hikikomori is the social isolation; the distinctive element is the sociospatial self-segregation of affected individuals, who are predominately adolescents and marginally young adults. 9 This form of physical isolation typically take place at home, where these persons spend most of the day avoiding exposure to any form of socialization (at school, sport centers, and similar socializing contexts) for days, weeks, or months.…”
Section: Definition Of the Hikikomori Disordermentioning
confidence: 99%